The automatic and manual railroad door systems based on IoT - Setiyo Budiyanto; Freddy Artadima Silaban; Lukman Medriavin Silalahi; Triyanto Pangaribowo; Muhammad Hafizd Ibnu Hajar; Alvin Sepbrian; Rachmat Muwardi; Gao Hongmin (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The automatic and manual IoT-based rail door (internet of things) is a door bar designed to be able to close and open automatically and manually. The automatic system works based on sensors that detect the presence of trains and system manual works based on the open and Close button on the smartphone. The components to be used are ATmega328 microcontrollers, infrared sensors, power supply, CCTV and android applications. Infrared sensor will detect the presence of the train and the gate will close automatically. Then the doorway will open when the train has crossed the automatic door bar. By the manual way, rail door control can be open and closed with Android smartphones in real-time with graphical display provided by CCTV. The whole process is connected to a WEB server where the program is embedded. Either it is automatic or manual control. From the tests that have been done, that the response data from the server is very fast, which is less than 1 second civil. For infrared sensor 1 there is an average delay of 0,687/sec and Infrared Sensor 2 is 3,449/sec. In realtime CCTV There is an average delay of 0,857/sec.